Supplement use of elite Australian swimmers - Shaw, G.; Slater, G.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
This study examined the influence the Australian Institute of Sport (AIS) Sport Supplement Program had on supplement practices of elite Australian swimmers, comparing those guided by the Program with others in the same national team. Thirty-nine elite swimmers (13 AIS, 26 Other; 20 female, 19 male; age 21.8 ± 3.3 y) completed a questionnaire investigating supplement use. Ninety-seven percent of swimmers reported taking supplements or sports foods over the preceding 12 months. AIS swimmers reported using more total brands (p = .02) and supplements considered Ergogenic (p = .001) than Other swimmers who used more supplements considered to be lacking scientific support (p = .028). Swimmers rated the risk of a negative outcome from the use of supplements available in Australia (Mdn = 3.0) as less than the risk of supplements from international sources (Mdn = 4.0; p < .001). AIS swimmers were more likely to report dietitians (p < .001) and sports physicians (p = .017) as advisors of their supplement use. Other swimmers more frequently reported fellow athletes as a source of supplement advice (p = .03). AIS swimmers sourced a greater percentage of their supplements from an organized program (94 ± 16%) compared with Other (40 ± 32%; p < .001) who sourced a greater percentage (30 ± 30%) of their dietary supplements from supermarkets. These findings suggest that swimmers influenced by this sport supplement program more frequently use supplements that are recommended by allied health trained individuals, classified as evidence based and provided by the program.